The application of proteins from less likely studied samples from South East Asia - Jaya Vejayan, Palliah (OMICS International - Open Access Publisher, 2016)
Protein play multitude of roles in the body of an organism. Enormous effort been done over the years to study proteins either by the tradition al chrumatography techniques of isolating one at a time or by the later developed means of proteomics advances capable to study direc tly on a protein mixture. This paper provides some examples of studies done on either of the mentioned approaches on protein mixtures obtained from samples specifically found predominantly in South East Asia. Expos mes on mapping the two dimensional electrophoresis gel of a number of venom from snakes found commonly in Malaysia and in its neighboring countries will be highlighted. The challenges of mapping protein of abundance, elimination of vertical streaks, lack of protein library, the use of cup loading spiking and 2DE guided purification techniques are some of the important findings. Additionally, the potential development of a protein marker capable to be used to authenticate herbal products incorporated with Tongkat Ali (the notoriously famous aphrodisiac plant) will be also introduced. To conclude the shift of attention from the traditional focus of investigating herbal constituents to that of bioactive protein in natural products rapidly emerging in South East Asia.